2017
DOI: 10.1126/science.aan2475
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetics revealed: DREADD occupancy and activation via converted clozapine

Abstract: The chemogenetic technology DREADD (designer receptors exclusively activated by designer drugs) is widely used for remote manipulation of neuronal activity in freely moving animals. DREADD technology posits the use of "designer receptors," which are exclusively activated by the "designer drug" clozapine N-oxide (CNO). Nevertheless, the in vivo mechanism of action of CNO at DREADDs has never been confirmed. CNO does not enter the brain after systemic drug injections and shows low affinity for DREADDs. Clozapine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
914
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 894 publications
(960 citation statements)
references
References 21 publications
37
914
8
1
Order By: Relevance
“…Importantly, CNO treatment had no effect on the behavior or body weight of Nts Cre ;NtsR1 ++ mice expressing channel rhodopsin (ChR) in LHA Nts neurons instead of hM3Dq-mCherry (Fig. S3), confirming that our results are not due to off-target effects of CNO or its metabolite clozapine (Gomez et al, 2017). Interestingly, activation of LHA Nts neurons in Nts Cre ;NtsR1 KOKO mice also induced sustained weight loss over 5 days (Fig.…”
Section: Resultssupporting
confidence: 70%
“…Importantly, CNO treatment had no effect on the behavior or body weight of Nts Cre ;NtsR1 ++ mice expressing channel rhodopsin (ChR) in LHA Nts neurons instead of hM3Dq-mCherry (Fig. S3), confirming that our results are not due to off-target effects of CNO or its metabolite clozapine (Gomez et al, 2017). Interestingly, activation of LHA Nts neurons in Nts Cre ;NtsR1 KOKO mice also induced sustained weight loss over 5 days (Fig.…”
Section: Resultssupporting
confidence: 70%
“…Additional work is needed to make AAV vectors more efficient to reduce their required dose, and to make compact cell-type specific promoters that work robustly in primates 24 . Finally, ongoing studies of the pharmacokinetics of CNO and clozapine 62 will enable the optimization of ligand dosing for DREADD activation or motivate the use of available alternative ligands 63 or chemogenetic receptors 64,65 . These improvements will facilitate the development and translation of ATAC as a paradigm for precise noninvasive control of neural circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has brought into question the exclusivity of CNO as the ligand for DREADDs and demonstrated that rodents are capable of CNO to clozapine back metabolism (Gomez et al 2017). While it has been shown that CNO is not significantly back metabolized to clozapine in mice, it is possible that the limited clozapine produced is sufficient to induce DREADD activity reported in Gomez et al, while being subthreshold for off-target effects (Guettier et al 2009).…”
Section: Discussionmentioning
confidence: 99%